2022
DOI: 10.5744/bi.2022.0015
|View full text |Cite
|
Sign up to set email alerts
|

Youth Mobility, Migration, and Health Before and After the Black Death

Abstract: Migration is driven by the young but despite this, few isotope studies focus on adolescent migrants or the intricatenature of their movement. Using a multi-analytical approach, the authors explore this mobility and the impact of urban living on the diet and health of adolescents from the pre-and post-Black Death periods of Northern England. Isotope analysis (carbon, nitrogen, oxygen, and strontium) and lead concentrations were measured in 63 adolescents (10–25 years) from three sites in medieval York and from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The lack of evidence for long-distance migration is in agreement with earlier mtDNA evidence in medieval British and Danish cohorts ( 41 ) but in contrast to genome-wide evidence of increased long-distance migration from medieval Trondheim ( 15 ). A recent isotope study also found that fewer adolescents moved into York from long distance following the Black Death, possibly because of the economic decline of York and the enforcement of labor laws ( 42 ). These results suggest that the pandemic had a variable impact on human mobility in European cities depending on their regional, socioeconomic, and political context and circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of evidence for long-distance migration is in agreement with earlier mtDNA evidence in medieval British and Danish cohorts ( 41 ) but in contrast to genome-wide evidence of increased long-distance migration from medieval Trondheim ( 15 ). A recent isotope study also found that fewer adolescents moved into York from long distance following the Black Death, possibly because of the economic decline of York and the enforcement of labor laws ( 42 ). These results suggest that the pandemic had a variable impact on human mobility in European cities depending on their regional, socioeconomic, and political context and circumstances.…”
Section: Discussionmentioning
confidence: 99%